2010
DOI: 10.1590/s1677-04202010000100006
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological adaptation and metal accumulation in water hyacinth from two tropical rivers

Abstract: The ecophysiological adaptations of water hyacinth (metal hyperaccumulator) under adverse environmental conditions are not yet clearly elucidated. This work evaluated photosynthetic pigments and chlorophyll a fluorescence in water hyacinth plants sampled in different regions (upper, middle and lower) of Paraíba do Sul river (PSR) and Imbé river, Brazil. Additionally Mn, Fe, Zn, Cu, Cr, Pb and Ni were quantified on the shoots and roots. Roots were the preferential site of metal accumulation. Cromium was not det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Statistical analysis indicated the Fv/F0 ratio as the more effective in discriminating the efficiency of the photosynthetic apparatus. Others authors have suggested the use of the Fv/F0 ratio, rather than the Fv/Fm ratio, for better discrimination of small differences in the PS II quantum yield (Paiva et al, 2009;Pereira et al, 2000;Sarajeva et al, 2007;Oliveira et al, 2009;Vitória et al, 2010). In contrast, Roháček (2002) reported that the Fv/ F0 ratio in healthy plants can vary between 4 and 6, suggesting that despite it decreases in sun plants during the rainy season, this could not be well correlated with a stressed condition, as the performance of PS II quantum yield proved to be .…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis indicated the Fv/F0 ratio as the more effective in discriminating the efficiency of the photosynthetic apparatus. Others authors have suggested the use of the Fv/F0 ratio, rather than the Fv/Fm ratio, for better discrimination of small differences in the PS II quantum yield (Paiva et al, 2009;Pereira et al, 2000;Sarajeva et al, 2007;Oliveira et al, 2009;Vitória et al, 2010). In contrast, Roháček (2002) reported that the Fv/ F0 ratio in healthy plants can vary between 4 and 6, suggesting that despite it decreases in sun plants during the rainy season, this could not be well correlated with a stressed condition, as the performance of PS II quantum yield proved to be .…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of toxic elements in the water hyacinth obtained from rivers located in different parts of the world as reported in literature are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Different reports with water hyacinth have shown that most of the metal up-taken by this plant species is accumulated preferentially in the roots (Soltan and Rashed, 2003;Lu et al, 2004;Paiva et al, 2009;Vitória et al, 2010). The accumulation of metals in the root system appears to minimize any major effect on the biomass production and to reduce the harmful symptoms (Verkleij and Prast, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…Paraíba do Sul river (PSR) is a tropical river of medium size with approximately 1,145 km length and a drainage basin of 55,400 km 2 that serves three of the most important and populated Brazilian States. As a consequence, their waters are in constant association with the anthropogenic substances of toxic nature, exposing especially aquatic biota to stressful conditions (Azevedo et al, 2004;Campaneli et al, 2010;Vitória et al, 2010). The investigations on the plant performance in the natural conditions are essential to access the life conditions in contaminated environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation